A signal overshoot suppression circuit for digital step attenuators. (March 2017) - Kocer, Fatih
Abstract: This paper presents a novel control circuit that eliminates signal overshoot inherent to digital step attenuators (DSA) during state transitions. With the addition of digital delay elements, transitions from attenuation state to insertion loss state is delayed with respect to the transition from the insertion loss state to the attenuation state. This prevents unintended signal leakage to the output, eliminating possible signal overshoot. Since this novel technique achieves signal overshoot suppression with a simple addition to the digital control circuit, it is area efficient, and can be applied to any digital attenuator without degrading its RF performance. To present its effectiveness, the proposed technique is employed in a 6-bit DSA. The resulting reduced-overshoot DSA is manufactured in a commercial 0.18 µm Silicon-On-Insulator (SOI) process. Measurement results show that this technique successfully suppresses the signal overshoot to less than 0.2 dB.